Knowledge, Attitude and Practice of Health Care Workers in Sulaimani Health Facilities in Relation to Medical Waste Management - Mohammed, Sarko Masood; Othman, Nasih; Hussein, Ali hattem; Rashid, Kamal Jalal (Kurdistan Journal of Applied Research, 2017)
Medical waste management is of crucial importance in health care facilities (HCF). In the present study, we assessed the knowledge, attitude and practices of medical waste management in an HCF of Sulaimani city, Kurdistan Region of Iraq. Using a self-administered questionnaire, we collected information on waste management practices from health care professionals (HCP) in 14 public and private hospitals and 10 primary health care centers of the city. Based on answers, total knowledge score on a 10-point scale was established. A total of 406 HCPs (of those, 261 women), average age 37.3 (SD ± 9.4) years participated. Just 20.3% have been trained on medical waste management. The total knowledge score ranged from 0 to 9 with a mean of 4.7 (SD ± 1.8). Factors which were significantly associated with the better knowledge score was male gender, having a high educational degree, being trained in waste management and has been in service for more than 5 years. 68% of HCPs followed the color coding system, 91% always/frequently disposed used sharps/needles to safety boxes, 79% always or frequently recapped needles, 49% reported experiencing at least one needle prick injury during their work but only 37% of them had reported the injury to a supervisor and only 4% of those injured had filled an injury form. There is a low average level of knowledge and the unsafe risky practices are quite prevalent in HCFs. Provision of appropriate training on dealing with medical waste is essential to promote safe practices among HCFs.